Heavy metal extractability and plant bioavailability from two sacrificial biosolids soils as influenced by intensive liming - Claassens, A.S. (Andries Stephanus), 1943- (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2005.